2021
DOI: 10.1063/5.0069452
|View full text |Cite
|
Sign up to set email alerts
|

A review of tidal energy—Resource, feedbacks, and environmental interactions

Abstract: Hawliau Cyffredinol / General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research.• You may not further distribute the material or use it for any profit-maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 139 publications
0
8
0
Order By: Relevance
“…Lewis et al (2021) performed a comprehensive global resource assessment and found that maximum flow velocities over 1 m s −1 are attained in less than 13% of the world's coastline, whilst only 3.6% feature flow speeds over 1.5 m s −1 . Neill et al (2021) identified that developing technologies for currents of 1.5 m s −1 would increase by 16 times the number of sites suitable for harnessing tidal stream energy compared to the present HATs design targeting at 2.5 m s −1 currents. For these low-to-medium resource locations, vertical axis turbines (VATs) arise as a suitable technology capable of operating efficiently in lowto-medium velocities and at lower tip-speed ratios, beneficial to lower risk of collision of fish (Castro-Santos and Haro 2015).…”
Section: Introductionmentioning
confidence: 89%
“…Lewis et al (2021) performed a comprehensive global resource assessment and found that maximum flow velocities over 1 m s −1 are attained in less than 13% of the world's coastline, whilst only 3.6% feature flow speeds over 1.5 m s −1 . Neill et al (2021) identified that developing technologies for currents of 1.5 m s −1 would increase by 16 times the number of sites suitable for harnessing tidal stream energy compared to the present HATs design targeting at 2.5 m s −1 currents. For these low-to-medium resource locations, vertical axis turbines (VATs) arise as a suitable technology capable of operating efficiently in lowto-medium velocities and at lower tip-speed ratios, beneficial to lower risk of collision of fish (Castro-Santos and Haro 2015).…”
Section: Introductionmentioning
confidence: 89%
“…In oceanography, tides are commonly defined as the periodic variations in sea level that occur due to the gravitational forces of the Sun and the moon. Tides contain potential energy associated with the vertical variations in sea level (tidal range) and kinetic energy, related to the horizontal motion of the tidal stream, and it is extracted by tidal current turbines [44,45].…”
Section: Tidal Energymentioning
confidence: 99%
“…In the case of using the tidal current approach, according to Bahaj [30], the power output of the marine current turbines can be calculated as a function of the density of the fluid, swept area of rotor blades and flow velocity Eq. ( 3) [44]…”
Section: Tidal Resource Assessmentmentioning
confidence: 99%
“…In recent years, a new piece of human engineering has been introduced to some estuaries: tidal stream turbines; devices built to pull kinetic energy from tidal currents. Tidal energy is currently considered one of the most predictable and reliable sources of renewable energy available, with research and development on extraction devices expanding rapidly, making implementation increasingly feasible (e.g., Vazquez and Iglesias, 2016;Yang and Copping, 2017;Qian et al, 2019;Khanjanpour and Javadi, 2020;Neill et al, 2021). Estuaries are particularly favorable for tidal energy harvesting as they often feature fast tidal currents (relative to the open ocean) and are close to land-based electric grid connection points (Xia et al, 2010;Vazquez and Iglesias, 2015;Dıáz et al, 2020;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%